Successful treatment of clear cell carcinoma of ovary during pregnancy: a case report - Ashok, Preethi; Kannan, Kalaichelvi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
The incidence of malignant ovarian tumor is rare during pregnancy. Most women hope to maintain the pregnancy and preserve fertility thus increasing the need for standard guidelines regarding surgery and chemotherapy for safe oncologic and fetal outcomes. Here we present a 30-years-old primigravida, diagnosed with bilateral ovarian mass during routine ultrasound imaging at 8 weeks of gestation. CA125 was 14.2 U/ml. MRI pelvis taken at 13 weeks showed bilateral complex cystic masses with internal septations. The patient underwent bilateral salphingo-oopherectomy and infracolic omentectomy during 18th week of gestation, the histopathology showing clear cell carcinoma with capsular invasion and microscopic omental deposit thus staged as IIIA. She was planned for adjuvant chemotherapy comprising of paclitaxel and carboplatin during the 21st week along with serial ultrasounds for fetal monitoring. After 5 cycles, at 37 weeks of gestation, she was taken up for elective LSCS followed by completion of surgery for ovarian malignancy, that is, hysterectomy with bilateral pelvic lymphadectomy. Endometrium showed gestational changes with all lymph nodes being negative for tumor deposits. A healthy male child weighing 3.4 kg was delivered. She was given 6th cycle of chemotherapy post-surgery and two years later, mother and baby are doing well and on regular follow up. Thus, the successful treatment of clear cell ovarian carcinoma in this woman with safe pregnancy outcomes can be attributed to timely diagnosis and feasibility of surgery and chemotherapy during second trimester.